Rancangan Bentuk Sambungan Transmisi Mesin Pengurai Sabut Kelapa Dengan Penggerak Mesin Sepeda Motor Berbasiskan Metode Design For Manufacture And Assembly (DFMA) - Habli, Mustafa; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research is aimed to design the shape of transmission connection between coconut husk decomposermachine and a motorcycle engine, so it can be operated in coconut plantation areas. Preliminary in thisresearch is based on Nuriyadi and Cahyono who designed and tested a coconut husk decomposer machine,which used and electric motor. If the decomposer of coconut husk machine is operated in a plantation area withno electricity, then this machine can not be operated. The purpose of this research is to modify the motorcycleas the engine driver of decomposers of coconut husk machine which as a means for transportation as well. Themethod in this research is used Design For Manufacture and Assembly (DFMA) to determine the design oftransmission connection form. The research result was revealed the assembly time of transmission connectionof coconut husk decomposer machine of 129.67 seconds and the efficiency of assembly time was 4.6%.Keywords: Motorcycle, DFMA, QFD, Efficiency assembly.